Treatment and outcome of patients with acute myocardial infarction and chronic lung disease: insights from the nationwide AMIS Plus registry. (3rd October 2022) - Beckmann, C; Foster-Witassek, F; Brutsche, M; Maeder, M T; Eberli, F; Roffi, M; Pedrazzini, G; Radovanovic, D; Rickli, H
Abstract: Introduction: Little is known about patients with acute myocardial infarction (AMI) and chronic lung disease (CLD). The aim of our study was to analyze risk factors, treatment, and outcome of AMI patients with CLD over the last 20 years using the nationwide AMIS Plus registry. Methods: All AMI patients enrolled in the AMIS Plus registry with data on CLD between January 2002 and December 2021 were included. Chronic lung disease was determined according to the definition used in the Charlson Comorbidity Index. Data on baseline characteristics, regular medication, immediate therapy within 24 hours, in-hospital interventions and treatments, in-hospital outcome, complications and discharge medication were analyzed using descriptive statistics and logistic regression. Results: Among 53, 680 AMI patients, 5.8% had a CLD. The CLD group included 26.6% female and 73.4% male patients. Gender distribution was similar in patients with and without CLD. Patients with CLD were significantly older (71.2 vs. 65.8 y; p<0.001), more frequently diagnosed with NSTEMI, had more comorbidities and were less frequently never smokers (17.4% vs. 35.3%; p<0.001) compared to patients without CLD. In addition, CLD patients were less likely to receive aspirin, P2Y12 inhibitors, beta-blockers, ACE inhibitors and statins (all p<0.001), and were also less likely to undergo percutaneous coronary interventions (68.7% vs. 82.5%; p<0.001). Median length of stay was 2 days longer for CLD patients. Patients with CLD had more major adverse cardiac and cerebrovascular events in-hospital (10.3% vs. 5.9%; p<0.001) and higher crude in-hospital mortality (8.3% vs. 4.7%; p<0.001). However, multivariable regression analysis showed that CLD was not an independent predictor for in-hospital mortality (OR 1.19 (95% CI 0.98–1.45), p=0.081). Conclusion: Patients with CLD were less likely to receive evidence-based medicine and had a worse in-hospital outcome compared to those without CLD. However, after adjustment, CLD was not an independent predictor of in-hospital mortality. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZeneca AG, Biotronik (Schweiz) AG